Implementation of the Village Asset Management System Policy in Realizing Good Governance in Pekalongan Regency - Budi Nugraha; Mafturrahman Mafturrahman; Aria Elshifa; Nurul Aisyah Putri; Sari Fitriani (Department of Public Administration, 2022)
This research examines the Implementation of the Village Asset Management System (SIPADES) Policy in Realizing Good Governance in the Village Government of Pekalongan Regency. This problem is interesting to study because at this time the village has room to carry out governance. The method used is descriptive qualitative. The data sources consist of primary data with a total of 5 informants and secondary data with 3 types of documents. Data collection techniques were carried out by means of library research, and field studies (observations, interviews, and documents). Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results of the study are that the implementation of village asset management policies in the Proto Village Government is still experiencing several obstacles. Among them, in the aspect of communication, there is still a lack of training and mentoring for the SIPADES application. Non-human resources are still lacking in the internet network. In the disposition aspect, village asset management policies are top-down in nature. In addition, in the bureaucratic aspect of implementing village asset management policies in the Proto Village Government, Pekalongan Regency, they are still experiencing problems in the form of the process of inputting assets. Inputting takes a long time. Efforts can be made by holding intense assistance to all village governments in Pekalongan Regency in operating the SIPADES application. Assistance must be ongoing so that the village government can take advantage of the SIPADES application in helping to realize good governance.